P36 An Advanced Physiological Monitoring Tool To Detect Treatment Failure In Hospitalised Patients With Acute Exacerbation Of Chronic Obstructive Pulmonary Disease (AECOPD). (19th November 2012) - Suh, ES; Mandal, S; Ramsay, MC; Harding, R; Thompson, A; Moxham, J; Hart, N
Abstract : Background: Acute exacerbations of COPD are associated with significant mortality and morbidity. Hospitalised patients with AECOPD often deteriorate symptomatically despite treatment. We have developed 2 nd intercostal space parasternal EMG (EMGpara ) as a measure of neural respiratory drive (NRD), with the aim of detecting clinical change in such patients. We hypothesised that change in NRD would be able to detect treatment failure in an unselected cohort of AECOPD patients. Methods: Patients with AECOPD were recruited at a central London teaching hospital within 12 hours of admission. Patients underwent EMGpara, spirometry and measurement of inspiratory capacity at least daily until medically fit for discharge. Modified Borg scale was recorded with each EMGpara acquisition. We assessed improvement and deterioration by two measures: 1) the responsible medical team was asked to report any deterioration or improvement in the patients' condition during the course of admission (Leidy et al, AJRCCM 2011) ; and 2) 2-point changes in Borg score were recorded as representing significant deterioration or improvement in dyspnoea (Ries et al, COPD; 2005) . Changes in EMGpara%max and neural respiratory drive index (ΔNRDI, where NRDI= EMGpara%max x respiratory rate) (Murphy et al, Thorax; 2011) during episodes of deterioration or improvement were analysed. Results: 65 patients were recruited. At admission, age was 71±10 years, male 46.2%, FEV1%predicted 32±15% (n=34), body mass index (BMI) 25.6±7.7 kg/m2, length of hospital stay 4 (IQR 2–5.75) days, admission COPD assessment tool (CAT) score 29 (IQR 25–33). There were 66(83%) episodes of improvement and 14(17%) episodes of deterioration as defined by physician opinion . There was a difference in the change in EMGpara%max between episodes of improvement and deterioration (ΔEMGpara%max= –2.00% vs +4.99%, p=0.01; ΔNRDI= –53/min vs 117/min, p=0.02). There were 54(65%) episodes of improvement and 29(35%) episodes of deterioration as defined by a 2-point change on the Borg scale. Again there was a difference in neural drive measures between improvers and deteriorators (ΔEMGpara%max= –3.94% vs +2.72%, p=0.002; ΔNRDI= –108/min vs 74/min, p<0.001) (Figure 1 ). Conclusions: Neural respiratory drive, as measured by parasternal muscle EMG, is effective in the detection of improvement and deterioration during AECOPD, and demonstrates potential as a physiological biomarker to monitor clinical change.